The Impact of Location and Device Coupling on the Performance of the Osia System Actuator. (2nd April 2022) - Fierens, Guy; Borgers, Charlotte; Putzeys, Tristan; Walraevens, Joris; Van Wieringen, Astrid; Verhaert, Nicolas
Abstract : Active transcutaneous bone conduction (BC) devices offer the benefit of improved power output compared to passive transcutaneous devices and remove the risk of skin infections that are more common in traditional percutaneous BC devices. Despite these advantages, more research is needed on implant location, device coupling, and their influence on device performance. This study is aimed at quantifying the extent to which certain parameters affect device output when using the Osia® system actuator. Parameters under study are (1) implant location, (2) comparison with the actuator of a state-of-the-art BC device, (3) bone undergrowth simulation, and (4) skull fixation. Five human cadaveric heads were implanted with the actuator at three different implant locations: (1) recommended, (2) posterior Osia® positions, and (3) standard Baha® position. At each location, the cochlear promontory velocity and the intracochlear pressure difference were measured. A percutaneous bone conduction actuator was used as a reference for the obtained measurements. Stimulation levels corresponded to a hearing level of 60 dB HL for frequencies between 250 and 6000 Hz. In addition, bone cement was used as a simulation for reactive bone growth. Results obtained in four heads indicate an improved power transmission of the transcutaneous actuator when implanted at the recommended position compared to the actuator of the percutaneous device on its respective recommended location when stimulating at an identical force level. A correlation was found between the promontory vibration and the actuator position, indicating that the same level of stimulation leads to higher promontory vibrations when the device is implanted closer to the ear canal. This is mainly reflected at frequencies higher than 1 kHz, where an increase was observed in both measurement modalities. At lower frequencies (<1 kHz), the power transmission is less influenced by the implant position and differences between the acquired responses are limited. In addition, when no rigid coupling to the skull is provided, power transfer losses of up to 30 dB can be expected.